Pengaruh Discount dan Kepercayaan Konsumen terhadap Keputusan Pembelian pada Pengguna TikTok Shop di Kota Medan - Diva Nedya Putri; Onan Marakali Siregar (Journal on Education, 2023)
This research aims to determine the influence of discounts and consumer trust on purchasing decisions at the TikTok Shop. The research method used is a quantitative method. The sample in the study was 100 respondents using a purposive sampling technique. The data collection technique uses a questionnaire. The analysis techniques used are instrument testing, classical assumption testing, multiple linear regression testing and hypothesis testing. The results of this research show that discounts have a significant positive effect on purchasing decisions, with a t-count value of 2.626 > 1.984 with a sig value of 0.010 < 0.05 and a regression coefficient value of 0.183. Consumer trust also has a significant positive effect on purchasing decisions, with a t-count value of 11.080 > 1.984 with a sig value of 0.000 <0.05 and a regression coefficient value of 0.617. In simultaneous testing, the discount variables and consumer trust had an influence simultaneously with a level of influence of 70.1%, while the remaining 29.9% was influenced by factors outside this research.